Frequency of Polycystic Ovary Disease in Adolescent - Nazish Gul, Najma Bibi, Maria Ghafoor, Rubina Babar, Fauzia Anbreen (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Polycystic ovary syndrome (PCOS) is the most common cause of chronic hyper androgenic anovulation and the single most common cause of infertility in young women. Anovulatory cycles are frequent in adolescents. The common signs of adult hyperandrogenism are less reliable in adolescents than in adults: hirsutism is in a developmental phase, and acne vulgaris is common. Objective: To determine the frequency of polycystic ovary disease in adolescent presented to outdoor. Study Design and Setting: This cross sectional study was carried out in the Department of Obstetrics & Gynecology, DHQ, Zanana Hospital, Dera Ismail Khan. Duration of Study: This study was conducted from 1st July 2019 to 31st December 2019. Subjects and methods: A total of 128 girls presenting to OPD due to irregular periods were included. Ultrasound was done to all participants under supervision of consultant gynecologist of 3 years post fellow ship experience. 5 ml venous blood samples was collected from all participants by a 3rd year resident and was subsequently sent to laboratory for androgen levels. Polycystic ovary disease as per operational definition was noted. Results: Age range in this study was from 14 to 20 years with mean age of 18.195±1.29 years, mean weight 52.898±4.92 Kg, mean height 1.571±0.08 meters and mean BMI was 21.557±2.80 Kg/m2. 19.5% patients were with family history of polycystic ovary disease. Polycystic ovary disease was seen in 7.8% patients. Practical implication: To determine the frequency of polycystric ovary disease in adolescent presented to outdoor. Conclusion: Polycystic ovarian syndrome is affecting the lives of young unmarried girls. The clinical manifestations are variable with obesity playing the key role. Keywords: Adolescent, Irregular period, Polycystic ovary syndrome, Frequency